How does changing pricing behavior affect inflation? Evidence from Euro Area microdata - Hukkinen Juhana; Viren Matti (SUERF - The European Money and Finance Forum, 2026)
Why did we fail to predict the acceleration and persistence of inflation since early 2021? Was it because our forecasting tools relied too much on a parameterization which reflected the long non-inflationary period? This note provides some evidence from new Euro area micro data that supports this notion by showing that key time series properties of the micro level panel data did change a lot along with the acceleration of inflation, and in a way which is hardly consistent with conventional Calvo pricing schemes. Moreover, we find that there have been strong state-dependent elements in the pricing schemes suggesting that past pricing errors are compensated later on. Thus, the more there is relative price dispersion, the more there is a need for corrective action which may even lead to overshooting properties in aggregate inflation.
​​​​​​​